Image - Action - Space. Situating the Screen in Visual Practice - Friedrich, Kathrin (De Gruyter, 2018)
Screen-based media, such as touch-screens, navigation systems or virtual reality applications merge images and operations and situate users in space both within and beyond the boundaries of the screen. This volume examines the linking of screen, space, and operation in fields such as remote navigation, architecture, medicine, interface design or film production.